Surgical Outcome Prediction Using a Four-Dimensional Planning Simulation System With Finite Element Analysis Incorporating Pre-bent Rods in Adolescent Idiopathic Scoliosis: Simulation for Spatiotemporal Anatomical Correction Technique - Tachi, Hiroyuki; Kato, Koji; Abe, Yuichiro; Kokabu, Terufumi; Yamada, Katsuhisa; Iwasaki, Norimasa; Sudo, Hideki (Frontiers in Bioengineering and Biotechnology, 2021)
An optimal surgical strategy for adolescent idiopathic scoliosis (AIS) is to provide maximal deformity correction while preserving spinal mobile segments as much as possible and obtaining a balanced posture. From a spatiotemporal deformity correction standpoint, we recently showed that anatomical four-dimensional (4D) spinal correction could be accomplished by curving the rod. In the surgical procedure, two rods are bent identically to confirm spinal anatomical alignment without referring to the intraoperative alignment of the deformity. Therefore, anatomically designed rods have been developed as notch-free, pre-bent rods for easier anatomical reconstruction. In addition to providing the best spinal instrumentation configurations as pre-bent rods, prediction of surgical outcome along with its biomechanical impact can be obtained by simulation of the surgical procedures with computer modeling. However, an objective model that can simulate the surgical outcome in patients with AIS has not been completely elucidated. The present study aimed to compare simulated deformity corrections based on our newly developed spatiotemporal morphological 4D planning simulation system incorporating pre-bent rods and actual deformity corrections in patients with AIS. A consecutive series of 47 patients who underwent anatomical posterior correction for AIS curves were prospectively evaluated. After multilevel facetectomy, except for the lowest instrumented segment, 11 types of pre-bent rods were used. Patient demographic data, radiographic measurements, and sagittal rod angles were analyzed within 1 week of surgery. Our simulation system incorporating pre-bent rods showed a significant correlation with the actual postoperative spinal alignment. The present study demonstrated the feasibility of our simulation system and the ability to simulate the surgical procedure using the pre-bent rods. The simulation system can be used to minimize the differences between the optimal and possible outcomes related to the instrumentation levels and rod shapes. Preoperative assumption of rod shape and length can contribute to a reduction in operative time which decreases blood loss and risk of infection. The results of the finite element analysis in the simulation system measured for each individual patient would also provide a more realistic representation of the surgical procedures.